Functional assessment of improvement of myocardial ischemia using coronary flow velocity reserve after coronary artery bypass surgery in hemodialysis. Issue 8 (18th June 2019) - Honda, Kentaro; Yuzaki, Mitsuru; Kaneko, Masahiro; Funahashi, Ryosuke; Kunimoto, Hideki; Fujimoto, Takahiro; Nakanishi, Yasuka; Agematsu, Kota; Nagashima, Mitsugi; Nishimura, Yoshiharu
Abstract: Background: In patients with end‐stage renal disease requiring hemodialysis (HD patients), myocardial ischemia after coronary artery disease is a major cause of mortality. Coronary pathophysiology, namely myocardial microvascular dysfunction, appears to differ from patients not requiring HD (non‐HD patients). Objectives: We compared functional improvement of myocardial ischemia after coronary artery bypass surgery (CABG) between HD and non‐HD patients by transthoracic coronary flow velocity reserve (CFVR). Methods: We retrospectively reviewed isolated CABG patients from between 2008 and 2017. Finally, 161 patients were enrolled; each underwent pre‐ and postoperative CFVR assessment, and left anterior descending (LAD) artery revascularization with "in‐situ" internal mammary artery (IMA). Graft patency was confirmed, and after successful CABG, postoperative CFVR improvement between the two groups was compared. Results: Preoperative CFVR value in group H was 1.81 ± 0.52, group N was 1.93 ± 0.66. There was no significant difference between the groups. IMA to LAD grafts were patent in postoperative evaluation in all patients. Postoperative CFVR in group H was 2.48 ± 0.72 and group N was 2.83 ± 0.73 ( P  = .042). Significant difference was observed. Conclusion: In both groups, CFVR values improved after successful CABG, but postoperative CFVR values were significant different. In younger populations CFVR values are generally higher. Our HD group was significantly younger than the non‐HD group, but CFVR values were postoperatively significantly lower. CFVR values are reportedly affected by both epicardial and microcoronary circulation. In this study population, as all grafts to the LAD were patent, the lower CFVR value in the HD group was considered to have resulted in microvascular disorders.